Phase-Selective Synthesis of CIGS Nanoparticles with Metastable Phases Through Tuning Solvent Composition - Xiaokun Zhang; Shuai Liu; Fang Wu; Xiaoli Peng; Baoguo Yang; Yong Xiang (Nanoscale Research Letters, 2018)
Abstract I-III-VI2 compounds have shown great interests in the application of functional semiconductors. Among them, Cu(In,Ga)S2 has been a promising candidate due to its excellent optoelectronic properties. Although the polymorphs of Cu(In,Ga)S2 have been attracted extensive attentions, the efforts to developing the methodologies for phase-controlled synthesis of them are rare. In this paper, we reported a phase-selective synthesis of CIGS nanoparticles with metastable phases via simply changing the composition of solvents. For the wet chemistry synthesis, the microstructure of the initial nuclei is decisive to the crystal structure of final products. In the formation of Cu(In,Ga)S2, the solvent environment is the key factor, which could affect the coordination of monomers and influence the thermodynamic conditions of Cu-S nucleation. Moreover, wurtzite and zincblende Cu(In,Ga)S2 nanoparticles are selectively prepared by choosing pure en or its mixture with deionized water as reaction solvent. The as-synthesized wurtzite Cu(In,Ga)S2 possess a band gap of 1.6 eV and a carrier mobility of 4.85 cm2/Vs, which indicates its potential to construct a heterojunction with hexagonal-structured CdS for solar cells.